Polar regions - Guillain, Charlotte (Chicago, Illinois Raintree, an imprint of Capstone Global Library, LLC, 2014)
They are absolutely frigid and often dark. They re also impossibly beautiful and full of interesting life. If you had the chance to explore the Polar Regions, what would you need to know? What would you pack? And who would you want to come with you? This book gives you the knowledge you need to plan your adventure!
A gift from book Africa
The World Around us
1 2 13 15
NEW_ZTN_GN
Keywords: JUVENILE NONFICTION -- People & Places -- Other; Polar regions -- Description and travel -- Juvenile literature